Socrates’ Three Filters and Bullying Prevention: An Exploratory Study of Ethical Speech in School Contexts - Kayro Panjaya; Juwaria Muqtadir (Insan Akademika Publications, 2026)
Bullying remains a persistent educational problem that threatens students’ well-being, classroom safety, and the moral climate of school life. Although many school-based anti-bullying strategies emphasize rules, supervision, counseling, and disciplinary responses, less attention has been given to the ethical quality of students’ everyday speech. Previous studies have examined bullying through behavioral, psychological, social-emotional, and school-climate perspectives, but the use of philosophical tools to help students evaluate speech before it becomes harmful remains underexplored. This study examines Socrates’ Three Filters of truth, goodness, and usefulness as a framework for strengthening ethical communication in bullying prevention. Using an exploratory qualitative-dominant design, the study combined a focused literature review with a small descriptive survey involving 10 upper-primary and lower-secondary students in an integrated basic education setting. The findings show that 90% of participants had witnessed or experienced bullying, 80% were unsure whether information shared in bullying-related comments was true, 50% were unsure whether they usually considered the necessity of their words before speaking, and 60% believed that applying the Three Filters could help reduce bullying. These findings suggest that harmful student communication is shaped not only by intentional aggression, but also by weak verification habits, limited reflection, and the normalization of unkind speech as honesty. The study contributes a conceptual-pedagogical framework that positions the Three Filters as a micro-ethical tool within broader school-based strategies. However, because the study involved a small, context-specific sample and did not test a formal intervention, its findings should be interpreted as exploratory rather than generalizable.